Effect of storage temperature and heat treatment on anthocyanin concentration of Solanum Melongena L. and its physical characteristic - Nadia Anwar (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
Anthocyanin (ACY) is the phenol compounds that widely distributed throughout nature. This compound is important because of their significant presence as natural source of colouring and its own potential health benefits. However, anthocyanin is unstable and easily degraded particularly when temperature is applied. The main objectives of this study were to synthesize anthocyanin pigment from eggplant and to analyze the effect of temperature to the concentration of anthocyanin. Anthocyanin extract was obtained from the skin of purple coloured eggplant (Solanum Melongena L.) using the solid phase extraction (SPE) with acidified ethanol. In this study, total monomeric anthocyanin, degradation kinetic and colour density were measured using spectrophotometric method. Monomeric anthocyanin concentration and colour density of anthocyanin were evaluated during storage at 3 C, 10 C, 25 C, 37 C and 50 C and heat treatment at temperature of 60 C, 70 C, 80 C, 90 C and 100 C. Total monomeric anthocyanin pigment was determined using pH differential method which was the approved method of Association of Analytical Chemist (AOAC). The results indicated that a lower storage temperature of 3 C had a lower degree of degradation than 50C while in heat treatment analysis, temperature of 60 C had lower degree of degradation compared to 100 C. Based on this study, a better understanding of anthocyanin synthesizing and anthocyanin stability at various temperatures was obtained which are essential to provide an additional information to food processing industry in Malaysia since anthocyanin has gained interest as one of the alternative source of colouring agent in food industry.